K.L. Johnson and contact mechanics - Nowell, D; Hills, D; Barber, J (SAGE Publications, 2016)
The Proceedings of the I.Mech.E. date back to 1847 and have appeared in various forms over the years. For those interested in the history of the Proceedings, a ‘timeline’ summary is provided by the current publishers, Sage, on their website [1]. In 1959, coincidentally when the second of the authors was born, the Journal of Mechanical Engineering Science was founded as a separate journal published by the Institution. In 1983, as part of a reorganisation of the Institution’s Journals, it became Part C of the proceedings. In this form it has continued to the present day, although publication transferred to Sage in 2010. Hence, in 2008 the journal was approaching its fiftieth anniversary. The chairman of the editorial board, as it was then constituted, Prof. Duncan Dowson FRS , came up with the idea of arranging some personal contributions from those who had been material in the journal’s success. In the end not many such articles appeared, but it was in response to this initiative that the authors spoke informally to Ken Johnson about his life and work . Typically modest in his approach, Ken was reluctant to see the article published during his lifetime, and so it has remained in the ‘bottom drawer of the desk’ ever since. But now, following Prof. Johnson’s passing in September 2015 we thought it appropriate to publish our brief article with minor modifications, and hope that it will serve as a memorial to the enormous contribution he made to his chosen field of study.